Temperature and Concentration Effects of Aqueous Solution of Sodium Octanoate on Micelle Formation Measured by Small angle X-ray Scattering - A.P. Kuzmenko; A.S. Chekadanov; U.A. Mirgorod; T.A. Dolenko; S.A. Burikov; M.B. Dobromyslov (Журнал нано- та електронної фізики)
Characteristic sizes of sodium octanoate micelles have been determined (by nucleus radius) with the use of small angle X-ray scattering technique at various molar concentrations, which are for a spherical shape 1 and nonspherical 1.2 nm, respectively. The value of the critical concentration for micelle formation (CMC2) has been also found equal to 0.7 M.